Development of a Mathematical Model for Obtaining Energy Characteristics of the Turbine Unit with the K-325-23.5 Steam Turbine - Taras Kravets; Hryhorii Riabokon (Energy Engineering and Control Systems, 2022)
The results of mathematical modelling of the turbine unit with the K-325-23.5 steam turbine are presented. The mathematical model of the turbine is a system of equations for the components of the heat-balance diagram and the main dependencies of its operating characteristics obtained through the thermal full-scale tests. The developed mathematical model allows adjusting the results of the full-scale tests, creating normative characteristics and conducting research of the intermediate modes of the turbine operation. It is suggested to obtain correction curves for the main parameters of the turbine unit by conducting a simulation experiment on a mathematical model of the turbine instead of carrying out real tests. The correction is done by a complete recalculation of the turbine and its thermal cycle, taking into account the characteristics of the components of the turbine unit and the conditions of its operation during the test. As a result, the main energy characteristics under different operating conditions have been obtained, in particular, correction curves of the main steam consumption and specific heat consumption for the deviation of the initial steam parameters and changes in the heat-balance diagram were built.